The presence of protozoal cysts and helminthic ova on Vegetables collected from Baghdad markets - Y., Guirges.; Al-mofti, Abdu waddood (Journal of the Faculty of Medicine Baghdad, 2005)
Summary The vegetables are considered as an important source of human infection with intestinal parasites. Aims: to try a detection of the protozoal cysts or helminthic ova from vegetables collected from Baghdad markets. Methods: The study was carried out during three months I’1 of September to the end of November 1999. Four different kinds of vegetables were selected for this study including tomato, onion, cucumber and celery. The vegetables soaked and washed in saline, centrifuged and the sediment examinedfor the presence ofprotozoal cysts, helminthic ova or fungi. Results: Ova of Ascaris lumbricoides and Enterobius vermicularis were isolated from tomato and celery. Hookworm ova were isolated from celery leaves. Entamoeba histolytica cysts were present on tomato, celery and cucumber. Giardia lamblia cysts found on tomato and celeiy. In addition, the monilia (Candida albicans) and Geotrichum candidum were isolated from tomato and celery. Conclusion: Vegetables may play an important role in intestinal parasites infection.